Mini Glider Design and Implementation with Wing-Folding Mechanism - Demircali, Ali Anil; Uvet, Huseyin (MDPI, 2018)
This paper describes a mini unmanned glider's design, simulation, and manufacturing with a novel wing-folding mechanism. The mini-glider is designed for CanSat competition, which has a theme of a Mars glider concept with atmosphere data acquisition. The aim is to facilitate the transportation of the glider and to land it on the destination point by following strict rules. Having a light and compact design is important since it uses power for the transmission of sensory data only. Dimensions of the glider is produced with a wingspan that is 440 mm and a length of 304 mm. The wings can be stowed in a fixed size container that has a diameter of 125 mm and a height of 310 mm. Its weight is only 144 g and it can increase up to 500 g maximum with a payload. The mechanism, which includes springs and neodymium N48 grade magnets for a wing-folding system, is capable of being ready in 98 ms for gliding after separating from its container. The mini-glider is capable of telemetering, communicating, and conducting other sensory operations autonomously during the flight.
Keywords: MAV; autonomous system; wing-folding; reconnaissance; UNMANNED AERIAL VEHICLES; Chemistry; Engineering; Materials Science; Physics